Analisis Kepuasan dan Loyalitas Konsumen Midori Japanaese Restaurant Cabang K.H. Wahid Hasyim Jakarta Pusat - Tintin Sarianti; Rr. Prita E Putriana (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2011)
Citizen consumption for the times towards food is more increase. This matter will be influenced by the increasing need of citizen on nutrition and nutrient. This phenomenon is followed by the existence of many restaurants as business caterers. Jakarta is one of the cities in Indonesia with a variety of diversity, including in terms of food. There are various kinds of foods sold in restaurants in Jakarta, both from within and outside the country. One of them is a unique Japanese food. Currently, there are more and more Japanese food restaurants in Jakarta. One of the restaurants that still survive until this day is Midori Japanese Restaurant. In maintaining its business, Midori Japanese Restaurant needed to explore its consumer characteristics, consumer satisfaction, and consumer loyalty. The restaurant can implement marketing strategies to maintain its business. This research was commenced from March to May 2010 and conducted at Midori Japanese Restaurant branch K.H. Wahid Hasyim Central Jakarta. This research used descriptive analysis for consumer characteristics, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA) to know the attributes improvements, and loyalty pyramid to determine the level of consumer loyalty. This research also provided recommendations that can be done as marketing strategy.Keywords: Japanese food, consumer characteristics, consumer satisfaction, consumer loyalty, descriptive analysis, Customer Satisfaction Index (CSI), Importance Performance Analysis (IPA), loyalty pyramid.